2022
DOI: 10.3389/fpsyt.2022.1058572
|View full text |Cite
|
Sign up to set email alerts
|

Screen time and depression risk: A meta-analysis of cohort studies

Abstract: BackgroundThe impact of screen time on mental health, including depression, has attracted increasing attention from not only children and adolescents but also the elderly. Thus, we conducted a meta-analysis of cohort studies to evaluate the association between screen time and depression risk.MethodsThe PubMed, Embase, Web of Science, and China National Knowledge Infrastructure databases were searched for cohort studies up to May 2022, and the reference lists of the included studies were also retrieved. A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…The current prospective findings on the incidence of BED at the two‐year follow‐up extend prior work showing a positive association between screen time and BED among adolescents (Fiechtner et al, 2018; Nagata et al, 2021). Moreover, replicating findings from prior studies, this investigation found that screen time was also prospectively associated with increased depression symptoms over 1 year (Boers et al, 2019; Li et al, 2022). However, different studies have yielded different results regarding the relationship between screen time and depression symptoms.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The current prospective findings on the incidence of BED at the two‐year follow‐up extend prior work showing a positive association between screen time and BED among adolescents (Fiechtner et al, 2018; Nagata et al, 2021). Moreover, replicating findings from prior studies, this investigation found that screen time was also prospectively associated with increased depression symptoms over 1 year (Boers et al, 2019; Li et al, 2022). However, different studies have yielded different results regarding the relationship between screen time and depression symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, screen time on social media may contribute to lowering self-esteem and increased depression symptoms in adolescents via upward social comparisons (i.e., comparing themselves to others who have more favorable social positions) (Li et al, 2022). Although not examined here, the role of social media screen time may be particularly relevant to eating disorders like BED, given potential impacts on other known risk factors such as body dissatisfaction and dietary restraint.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations